MicroRNA-214 modulates the senescence of vascular smooth muscle cells in carotid artery stenosis - Yi-Ling Chen; Jiunn-Jye Sheu; Cheuk-Kwan Sun; Tien-Hung Huang; Yuan-Ping Lin; Hon-Kan Yip (Molecular Medicine, 2020)
Abstract Background MicroRNAs control gene expression by post-transcriptional inhibition. Dysregulation of the expressions of miR-199a/214 cluster has been linked to cardiovascular diseases. This study aimed at identifying potential microRNAs related to vascular senescence. Methods Seven candidate microRNAs (miR-19a, −20a, −26b, −106b, − 126, − 214, and − 374) related to cell proliferation were tested for their expressions under CoCl2-induced hypoxia in vascular smooth muscle cells (VSMCs). After identification of miR-214 as the candidate microRNA, telomere integrity impairment and cell cycle arrest were examined in VSMCs by using miR-214 mimic, AntagomiR, and negative controls. To investigate the clinical significance of miR-214 in vascular diseases, its plasma level from patients with carotid artery stenosis (CAS) was assessed by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR). Results CoCl2 treatment for 48 h suppressed cell proliferation and angiogenesis as well as enhanced cell senescence in VSMCs. Besides, miR-214 level was elevated in both intracellular and exosome samples of VSMCs after CoCl2 treatment. Manipulating miR-214 in VSMCs demonstrated that miR-214 not only inhibited angiogenic and proliferative capacities but also promoted senescence through the suppression of quaking. Additionally, circulating miR-214 level was upregulated in CAS patients with high low-density lipoprotein cholesterol (LDL-C) value. Conclusion Our findings suggested that miR-214 plays a role in the modulation of VSMC angiogenesis, proliferation, and senescence with its plasma level being increased in CAS patients with elevated LDL-C value, implying that it may be a vascular senescence marker and a potential therapeutic target for vascular diseases.